Ambition, federalism, and legislative politics in Brazil - Samuels, David 1967- (Cambridge University Press, 2003)
Ambition theory suggests that scholars can understand a good deal about politics by exploring politicians' career goals. In the USA, an enormous literature explains congressional politics by assuming that politicians primarily desire to win re-election. In contrast, although Brazil's institutions appear to encourage incumbency, politicians do not seek to build a career within the legislature. Instead, political ambition focuses on the subnational level. Even while serving in the legislature, Brazilian legislators act strategically to further their future extra-legislative careers by serving as 'ambassadors' of subnational governments. Brazil's federal institutions also affect politicians' electoral prospects and career goals, heightening the importance of subnational interests in the lower chamber of the national legislature. Together, ambition and federalism help explain important dynamics of executive-legislative relations in Brazil. This book's rational-choice institutionalist perspective contributes to the literature on the importance of federalism and subnational politics to understanding national-level politics around the world